CORRELATIONAL RESEARCH DESIGN - Putri, Lyindira; Muhammad Rizki Rezani; Dina Hermina (PT. Hasba Edukasi Mandiri, 2025)
Correlational research is a methodological approach that aims to identify and analyze the relationship between two or more variables without manipulation. This article aims to comprehensively explain the basic concepts of correlational research, its objectives, characteristics, design types, and limitations. The method used in this study is library research with an analytical-critical approach to various relevant academic literature. The results show that correlational research not only identifies the existence of relationships between variables but can also be used for predictive purposes through regression analysis and multiple regression. The types of correlational designs discussed include bivariate correlation, path analysis, cross-lagged panel, and factor analysis. On the other hand, the main limitation of this approach lies in its inability to explain causal relationships and the tendency for biased data interpretation if not analyzed carefully. By understanding the characteristics and weaknesses of this method, researchers are expected to be able to use it appropriately in various social and educational research contexts.